Voices of writing- in times of children and minstrels - Belintane, Claudemir (Clinical Styles. The Journal on the vicissitudes of childhood, 2008)
Through this article one intends to show that a good deal of reflections about concepts of letter and writing - having as a reference the history of writing - which, in spite of overcoming the idea of existence of development phases which succeed each other, both on a sociogenetical and an ontogenetical basis, conceived mostly as a communication code, still approach letter and writing without taking into account its recurrent conflicts with oral cultures. This work proposes a reflection considering both the conflicts between oral and writing cultures and the possible relations between textual genders in infancy and the learning of writing.